Design and analysis of microelectromechanical (MEMS) vibration isolator - Rohit Singh. (2012)
With continued miniaturization of electronic components and the need for reduction in costs, Microelectromechanical systems (MEMS) have attracted the interest of electronics industries for many years. The application of the modern technology of MEMS oscillators to replace the traditional Quartz-based oscillators, has given a new direction to electronic timed applications. Providing low cost and high reliability at large volumes for the consumer electronic market has been a target for MEMS industries since the last decade.